Is it possible to detect active multiple sclerosis plaques using MR thermometry techniques? - Demir, Caner Feyzi; Inci, Mehmet Fatih; Ozkan, Fuat; Ozdemir, Hasan Huseyin (Churchill Livingstone, 2013)
Multiple sclerosis lesions or plaques are considered to be the result of an inflammatory process in the brain that leads to attack myelin. Inflammation causes disruption of blood-brain barrier in acute, active plaque areas. This process may lead to increase blood supply that causes increase in temperature in these associated areas. These plaques can be seen by examining the brain using magnetic resonance imaging (MRI). Presence of these plaques plays an important role in indicating dissemination in time within the new diagnostic criteria and in treatment of active MS. Gadolinium-based contrast agents help for quantitative assessment of inflammatory activity and lesion load. However, these agents have serious risks such as anaphylaxis and kidney damage. We wanted to open up a discussion for the feasibility of using noninvasive MR thermometer technique instead of conventional MRI techniques, for evaluating the temperature and the extent of temperature changes of white matter and plaques in MS patients. After successful using of MR thermometer technique with upgraded applications, the time needed to perform the studies in a routine setting can be significantly shortened. With eliminating usage of contrast agent, considerable influx money can be provided along with preventing the adverse effects and risks of contrast agent usage. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nephrogenic Systemic Fibrosis; Magnetization-Transfer; Enhanced Mri; Tissue-Type; Temperature; Gadolinium; Sensitivity; Frequency; Lesions; Mechanisms